2008
DOI: 10.1007/s00066-008-1787-5
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Cancer

Abstract: Survival was excellent especially for patients without nodal disease in this dose-intensified schedule with acceptable tolerability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The mentioned trials were conducted prior to the era of IMRT and IGBT. The trial results were confirmed through an additional prospective trial from Brunner et [ 77 ]. Current BT trials for ECa are focusing on palliation.…”
Section: Discussionmentioning
confidence: 70%
“…The mentioned trials were conducted prior to the era of IMRT and IGBT. The trial results were confirmed through an additional prospective trial from Brunner et [ 77 ]. Current BT trials for ECa are focusing on palliation.…”
Section: Discussionmentioning
confidence: 70%
“…It also allows rapid relief in dysphagia due to high dose to the tumour bed. Brunner et al 16 delivered HDR brachytherapy sandwiched with EBRT with the hypothesis that a better dose coverage is expected due to decreased tumour thickness.…”
Section: Ilrtresultsmentioning
confidence: 99%